Clinical trials of transcatheter aortic valve replacement. (7th March 2019) - Al-Azizi, Karim; Hamandi, Mohanad; Mack, Michael
Abstract : Transcatheter aortic valve replacement(TAVR) has emerged as an effective treatment option in patients with severe aortic stenosis, in large part due to a robust evidence base generated by a series of randomised controlled trials (RCTs). During the past decade more than 15 000 patients have been randomised worldwide in nine clinical trials, mostly for regulatory approval in the USA, making it one of the most carefully scrutinised medical devices at the time of introduction into clinical practice. Initial trials were performed in inoperable or extreme risk patients compared to medical therapy and demonstrated superiority. Subsequent RCTs compared TAVR to surgical aortic valve replacement in high and intermediate surgical risk patients and TAVR was found to be non-inferior in all studies. RCTs of low surgical risk patients have completed enrolment and 1 year outcomes will be available in early 2019. The details of the trials, trial results, outcomes and remaining clinical questions are summarised in this article.